Potential for iron enriched yeast in recovery of rats from iron deficiency - Kyyaly, Aref; Powell, Chris (2015)
It is well known that iron deficiency can lead to anemia, resulting in a variety of symptoms and health issues. Negative effects can be prevented by ensuring foods with a naturally high iron content are ingested, or countered by taking nutrient supplements. As an alternative it is possible to influence the nutritional content of foods to ensure that dietary requirements are met. In this study we aimed to evaluate the potential for using iron-enriched baker’s yeast as a source of iron for curing and protection against anemia. Iron enriched yeast was prepared by growing cells on basal medium containing different concentrations of iron. Iron accumulation in yeast cells and dough leavening power increased with iron concentration and reached a maximum of 15 mg/g and 45 cm respectively, when 32 mM Fe was applied. The effects of enriched yeast on animal health were assessed by feeding anemic rats with a variety of diets containing either inorganic iron or iron enriched yeast. Body weight, iron bioavailability, blood parameters, and iron containing enzyme activity (Catalase) were studied. Groups fed on iron enriched yeast gave the highest feed efficiency, iron bioavailability and hemoglobin concentration. Different treatments raised the Catalase activity from 70 U/g tissue in anemic rats to 90 U/g tissue (iron salt added), 110 U/g tissue (iron salt and dry yeast added), 145 U/g tissue (iron enriched yeast 15 mg Fe/g diet added) and 115 U/g tissue (iron enriched yeast 30 mg Fe/g diet added). The histological study of tissues from liver, kidney, heart, and spleen of rats from different groups showed that the severe damage observed in tissues of anemic rats, was completely recovered after treatment by feeding with iron enriched yeasts, However salt-based treatments required more time to achieve the same results It is suggested that the use of iron-enriched yeast products may lead to the prevention of anemia in compromised individuals, or the ability to recover from moderate iron deficiency